1996
DOI: 10.2307/4002881
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Mule Deer Diet Quality and Intake with Fecal Indices

Abstract: Few studies have evaluated fecal indices for monitoring diet quality and intake of North American deer. We conducted 11 digestion trials with black-tailed (Odocoileus hemionus columbianus Richardson) and mule deer (0. h. hemionus Rafmesque) to examine relationships between several chemical constituents of deer feces (i.e., fecal nitrogen, fecal 2,6diaminopimelic acid (DAPA), fecal neutral detergent fiber (NDF), fecal acid detergent fiber, and fecal acid detergent lignin) and dry matter intake, digestible energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
61
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 33 publications
(27 reference statements)
4
61
0
Order By: Relevance
“…Since protein content and digestibility are positively correlated in plants (Robbins 1983), faecal nitrogen (FN) is therefore a common index that is correlated with the intake of proteins and dietary digestibility (Leslie and Starkey 1985;Hodgman et al 1996). FN has been widely used as an index of dietary quality in the Communicated by C. Gortázar * Antonio J. Carpio carpio86@hotmail.com 1 nutritional ecology of free-ranging and captive ruminants (Hamel et al 2009;Leslie et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since protein content and digestibility are positively correlated in plants (Robbins 1983), faecal nitrogen (FN) is therefore a common index that is correlated with the intake of proteins and dietary digestibility (Leslie and Starkey 1985;Hodgman et al 1996). FN has been widely used as an index of dietary quality in the Communicated by C. Gortázar * Antonio J. Carpio carpio86@hotmail.com 1 nutritional ecology of free-ranging and captive ruminants (Hamel et al 2009;Leslie et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Islam et al [2011] reported a high correlation between NDVI and nitrogen content of maize plants, but only at one specific phenological stage (8-leaf stage). Other studies linked NDVI with faecal crude protein (FCP) of large herbivores, which is considered a reliable indicator of the quality of vegetation [Cordova et al, 1978;Leslie and Starkey, 1985;Hodgman et al, 1996]. For example, Ryan et al [2012] showed a positive relationship between log transformed NDVI and nitrogen faecal content of African Buffalo (Syncerus caffer) and Hamel et al [2009] found a negative relationship between integrated NDVI in June and the date of the peak in FCP of mountain goats (Oreamnos americanus) and bighorn sheep (Ovis canadensis).…”
Section: Introductionmentioning
confidence: 99%
“…Because N is an element of the amino acids that make up proteins, it is the most common constituent used to evaluate the nutritional quality of the diet of wild (Leslie and Starkey 1987;Irwin et al 1993;Hodgman et al 1996;Blanchard et al 2003) and domestic ruminants (Arman et al 1975;Moore et al 2004). This is positively correlated with the digestibility of the diet as well (Irwin et al 1993).…”
Section: Introductionmentioning
confidence: 95%